Karakter Agronomi dan Potensi Hasil 10 Genotipe Padi Tipe Baru pada Dua Lingkungan Tumbuh Berbeda - Dulbari, Dulbari; Sa’diyah, Nyimas; Kamal, Muhammad; Tianigut, Gut (Politeknik Negeri Lampung., 2018)
The purpose of this study was to evaluate the agronomic characters and yield potential of ten new plant type (NTP) of rice genotypes planted on two different agroecologies. The study was done in East Lampung (Ultisols soil type, altitude 60 m asl, and average daily temperature 26,86°C) and Tanggamus (Andisols soil type, altitude 600 m asl, and average daily temperature 24.15°C) in January—Juni. The research was arranged in randomized complete block design (RCBD) with 12 treatments and 3 replications. The treatment consisted of 10 new type of rice genotypes, i.e., IPB 3S, IPB 4S, IPB 5R, IPB6R, IPB117-F-7-2-1, IPB 117-F-7-7- 1, IPB 117-F-14-4-1, IPB 117-F-15-4-1, IPB 117-F-20-1-1, IPB 117-F-80- 2-1, and two varieties, i.e., Ciliwung and Ciherang as control. The results showed that all NPT genotypes had lower number of tillers but the hill height were taller than the Ciliwung and Ciherang varieties. Eight genotypes had a faster harvesting time, and one genotype had a higher yield than two control varieties.